2014
DOI: 10.1016/s2214-109x(13)70160-8
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of a behaviour-change intervention on handwashing with soap in India (SuperAmma): a cluster-randomised trial

Abstract: Wellcome Trust, SHARE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
273
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(289 citation statements)
references
References 26 publications
7
273
1
8
Order By: Relevance
“…Most studies found handwashing rates to increase if the household had a water connection, 15,19,52 whereas others could not find this association. 53 The lack of association between the time spent collecting water and reported handwashing practices in this study might also be due to the breakdown of the sample into two groups, that is water collection time above 30 minutes per roundtrip and below 30 minutes, which may have hindered detecting an effect of the time spent collecting water on handwashing practices. Although a number of studies suggest that access to water may play an important role in reducing childhood diarrhea, there is a need for better designed studies to further elucidate the impact of the distance that people have to carry water home on hygiene practices and health.…”
Section: Discussionmentioning
confidence: 79%
“…Most studies found handwashing rates to increase if the household had a water connection, 15,19,52 whereas others could not find this association. 53 The lack of association between the time spent collecting water and reported handwashing practices in this study might also be due to the breakdown of the sample into two groups, that is water collection time above 30 minutes per roundtrip and below 30 minutes, which may have hindered detecting an effect of the time spent collecting water on handwashing practices. Although a number of studies suggest that access to water may play an important role in reducing childhood diarrhea, there is a need for better designed studies to further elucidate the impact of the distance that people have to carry water home on hygiene practices and health.…”
Section: Discussionmentioning
confidence: 79%
“…A study conducted in India showed that interventions that were based on understanding local context and drivers of handwashing behavior significantly increased handwashing with soap at key event times (1% in baseline to 37% in 6-month follow-up visit) including during food preparation. 22 One study that we could identified, conducted in Mali, described the process of preparation for two food items and related hygiene practices. 23 However, generally, there are limited data on food preparation steps and related handwashing practices that can inform behavior change interventions and pinpoint when hands should be washed during food preparation, especially from low-income contexts where easy access to running water is uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…18 In addition to the hardware described above, a comprehensive behavior change package using techniques recently found to be effective in India 19 was deployed by trained health promoters called intervention assistants (IAs) with the aim of promoting and sustaining behavior change among intervention households.…”
Section: Introductionmentioning
confidence: 99%